2020
DOI: 10.1088/1748-9326/ab87d2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of Euro-Atlantic teleconnections from multiple systems

Abstract: Seasonal mean atmospheric circulation in Europe can vary substantially from year to year. This diversity of conditions impacts many socioeconomic sectors. Teleconnection indices can be used to characterize this seasonal variability, while seasonal forecasts of those indices offer the opportunity to take adaptation actions a few months in advance. For instance, the North Atlantic Oscillation has proven useful as a proxy for atmospheric effects in several sectors, and dynamical forecasts of its evolution in wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…This skill is directly associated with the skill found for the SLP, with the systems showing a higher SLP regional skill having higher skill for the cluster frequency. Nevertheless, there are additional factors that can also play a role on the low skill in that area, such as the short hindcast length (1993–2016) or the limited ensemble size (from 40 to 25 members depending on the system) of the C3S seasonal forecast systems available (Scaife et al ., 2014; Manzanas et al ., 2019; Lledó et al ., 2020). The sensitivity of the skill to simulate the frequency of occurrence of the clusters depending on the ensemble size and the hindcast period has been tested (Figure S15) for the ECMWF‐S5 seasonal forecast system.…”
Section: Discussionmentioning
confidence: 99%
“…This skill is directly associated with the skill found for the SLP, with the systems showing a higher SLP regional skill having higher skill for the cluster frequency. Nevertheless, there are additional factors that can also play a role on the low skill in that area, such as the short hindcast length (1993–2016) or the limited ensemble size (from 40 to 25 members depending on the system) of the C3S seasonal forecast systems available (Scaife et al ., 2014; Manzanas et al ., 2019; Lledó et al ., 2020). The sensitivity of the skill to simulate the frequency of occurrence of the clusters depending on the ensemble size and the hindcast period has been tested (Figure S15) for the ECMWF‐S5 seasonal forecast system.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns, such as the North Atlantic Oscillation, can be directly linked to surface weather variables, but are often easier to predict (Lledó et al, 2020 ).…”
Section: Seasonal Temperature Forecastsmentioning
confidence: 99%
“…Despite the popularity of pattern-based methods to understand and predict the large-scale atmospheric circulation, they are associated with the key caveat that skill in forecasting the large-scale meteorological pattern (typically observed in 500 hPa geopotential height or surface pressure) does not in itself guarantee skill in terms of predicting a desired surface impact response (e.g., nearsurface wind speeds or temperatures, wind power generation or electricity demand). Recent work using historic reanalyses has, however, convincingly demonstrated that many Euro-Atlantic weather patterns (with various methods of construction) relate to relevant surface weather conditions (Bloomfield, Brayshaw, & Charlton-Perez, 2020a;Cortesi et al, 2019;Drücke et al, 2020;Garrido-Perez et al, 2020;Grams et al, 2017;Thornton et al, 2017;van der Wiel et al, 2019) and to European electricity demand, wind and solar power generation (Bloomfield, Brayshaw, & Charlton-Perez, 2020a;Grams et al, 2017;Lled o et al, 2020;van der Wiel et al, 2019). This suggests that, given these patterns can be forecast at lead times out to 2 weeks and 3 months for WRs and teleconnections respectively, they could potentially offer benefits over grid-point forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the science within the meteorological community has focused on the skill present in forecasts of Euro‐Atlantic teleconnections at seasonal timescales (Lledó et al, 2020) such as the North Atlantic Oscillation (NAO; Baker et al, 2018; Dunstone et al, 2016; Scaife et al, 2014) and Euro‐Atlantic WRs at sub‐seasonal timescales (Büeler et al, 2020; Charlton‐Perez et al, 2018; Ferranti et al, 2015; Matsueda & Palmer, 2018). Forecast skill for the daily occurrence of WRs has, for example, been shown to extend to approximately 2 weeks for sub‐seasonal forecasts (Ferranti et al, 2018; Matsueda & Palmer, 2018) with similar results found for WRs over North America (Robertson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation